Giving voice to the voiceless: Presentation of Labor Issues in Editorials of Elite Newspapers (2013-2018) - Raza, Amer; Muhammad Rashid Khan (Journal of Peace, Development and Communication, 2022)
Labor leaders and trade unionists often complain that newspapers do not give a proper presentation to labor issues. This research article is an effort to address their complaint and investigate the presentation of labor issues in the editorials of elite newspapers of Pakistan (Dawn and the News) from 2013-2018. Editorials present the case of the voiceless segment of society, and they also reflect general trends of coverage on news pages, because the editorials are written on important events and issues which emerged on news pages. They also present newspaper policy and generate debate in society on important issues. The selected newspapers have great importance in the public discourse of Pakistan, and they are read by the most influential segments of society. The period under the study was very eventful for labor in Pakistan. It is a quantitative and qualitative content analysis of editorials written on selected labor issues (trade unions and workplace security) by selected newspapers during the period under study. Applying the theory of agenda setting and framing the study has found that newspapers have given a very insufficient presentation to labor issues, but they positively presented the labor issues.